Plasma Fibroblast Growth Factor 23 Is Elevated in Pediatric Primary Hypertension - Lin, Yao; Shi, Lin; Liu, Yanyan; Zhang, Hongwei; Liu, Yang; Huang, Xiaolan; Hou, Dongqing; Zhang, Mingming (Frontiers in Pediatrics, 2019)
Fibroblast growth factor 23 (FGF 23), an endocrine hormone regulating the homeostasis of phosphate and vitamin D, has been shown to play a role in cardiovascular disease. Increased blood FGF 23 is found to be associated with elevated blood pressure in adults. However, measurement of FGF 23 in hypertensive children has not been documented. In this study, a total of 98 children with primary hypertension and 37 controls were recruited, and blood FGF 23 was comparatively investigated. Additionally, FGF 23 levels were compared between the subgroups of patients after hypertensive children were subgrouped according to their cardiac geometry, hypertension stages, insulin levels and weight. The case group had a FGF level of 48.99 (16.42) expressed as median (the interquartile range), significantly higher than 41.72 (7.05) in the control group (p = 0.0002). While no remarkable differences were observed in FGF 23 levels between non-obese and obese hypertensive children, between patients with stage I and stage II hypertension, or between patients with normal and high insulin levels; hypertensive children with abnormal cardiac geometry had significantly higher levels of FGF 23 than patients with normal cardiac geometry (p = 0.0085). Our data revealed for the first time that hypertensive children have higher levels of FGF 23. Further studies are in need to examine if lowering FGF 23 improves the cardiac geometry in hypertensive children with higher FGF 23.